Technological evaluation of four sugarcane cultivars as a function of Diatraea saccharalis infestation in Pedro Afonso, TO - case study (Research, Society and Development, 2022)
The objective of the present work was to evaluate the technological quality of four sugarcane (Saccharum spp.) cultivars as a function of I.I. (Intensity of Infestation) of sugarcane borer (Diatraea Saccharalis). The design used was completely randomized with four treatments (CTC9001BT, CTC20BT, CTC9001 and RB975952) and six replications. The parameters evaluated were I.I. (Intensity of Infestation), °Brix (Contents of Soluble Solids), TCH (Total Sugarcane per Hectare), Fiber, Purity and Pol Broth (Apparent Sucrose). In I.I. (Intensity of Infestation) of Diatraea Saccharalis, cultivars CTC9001BT and CTC20BT showed the lowest percentages, with 0.71% and 0.89% respectively. In °Brix (Contents of Soluble Solids), there was no difference. In TCH (Total Sugarcane per Hectare), the CTC20BT variety had the highest result with an average of 79.63 t/h. In Fiber, cultivars CTC9001BT and RB975952 presented the highest averages, 12.86% and 13.09% respectively. Purity and Pol Broth (Apparent Sucrose) had no significant differences. In this study, different infestations of Diatraea Saccharalis had little influence on the technological quality of sugarcane varieties. Parameters such as °Brix (Contents of Soluble Solids), Purity and Pol Broth (Apparent Sucrose), had no differences, since the variables that differed were TCH (Total Sugarcane per Hectare) and Fiber.